Visualization of four-dimensional X-ray absorption fine structure data using a virtual reality system - Haruo Igarashi; Daiki Kido; Yutaka Ishii; Yasuhiro Niwa; Atsushi Okamoto; Masao Kimura (Journal of Synchrotron Radiation)
X-ray spectromicroscopy is extensively utilized for nondestructive mapping of chemical states in materials. However, understanding and analyzing the geometric and topological aspects of such data pose challenges due to their representation in 4D space, encompassing (x, y, z) coordinates along with the energy (E) axis and often extending to 5D space with the inclusion of time (t) or reaction degree. In this study, we addressed this challenge by developing a new approach and introducing a device named `4D-XASView', specifically designed for visualizing X-ray absorption fine structures (XAFS) data in 4D (comprising 3D space and energy), through a multi-projection system, within the virtual reality (VR) environment. As a test case for the new system, X-ray spectromicroscopy measurements were conducted on a specimen prepared from serpentinized harzburgite sourced from the upper mantle section of the Oman ophiolite. Our 4D-XASView facilitates the visualization and analysis of the geometric and topological aspects of the data using VR goggles, enabling detailed exploration of microstructures via rotation and zooming functionalities. This capability allows us to extract XAFS spectral data by selecting specific positions and regions, thereby aiding in the identification of `trigger sites' (magnetite in serpentine), which are characteristic locations within materials that substantially influence the macroscopic propagation of reactions. Our methodology establishes a new platform for analyzing 4D or 5D XAFS data that has applicability potential in various other multidimensional datasets, including microstructures coupled with spectroscopy and diffraction data.